IMPACT OF DEBT TO EQUITY RATIO AND NET PROFIT MARGIN ON THE PRICE EARNINGS RATIO OF PT INDOFOOD SUKSES MAKMUR, TBK - Meiliani Luckieta (Jurnal Ekonomi, 2023)
Food and beverage companies in Indonesia are one of the business sectors that continue to experience growth and are also one of the categories of the industrial sector on the Indonesia Stock Exchange (IDX) which has opportunities to grow and develop so that competition between food and beverage companies is getting tighter, this is in line with the increasing population growth in Indonesia. The purpose of this study is to determine the overview and analysis of Debt to Equity Ratio, Net Profit Margin and Price Earnings Ratio at PT Indofood Sukses Makmur, Tbk for the period 2008-2017. The research methods used are descriptive methods and verifiable methods using the Multiple Linear Regression statistical test. The results showed that the Debt to Equity Ratio of PT Indofood Sukses Makmur, Tbk was not included in the Good category in that period. Meanwhile, Net Profit Margin and Price Earnings Ratio are included in the Good category. Then in testing the influence between variables, the results were obtained that the Debt to Equity Ratio and Net Profit Margin did not affect the Price Earnings Ratio either partially or simultaneously. The results of this study are expected to be useful for investors as an illustration of the condition of PT Indofood Sukses Makmur, Tbk as one of the companies listed in the LQ45 food and beverage sub-sector in Indonesia.